ANALISIS INOVASI PELAYANAN PUBLIK PADA ADMINISTRASI KEPENDUDUKAN MELALUI KADOKU SEHATI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SUMBAWA BARAT - KARTAPATI, KARTAPATI; UMAR, UMAR; KHADAFIE, MUAMMAR (Universitas Mahasaraswati K. Mataram, 2023)
In the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform of the Republic of Indonesia Number 30 of 2014 concerning Guidelines for Public Service Innovation it is stated that: